Calibrated helium and carbon ion flow measurements in the DIII-D divertor plasma. (May 2019) - Allen, S.L.; Samuell, C.M.; Meyer, W.H.; Jaervinen, A.E.; Porter, G.D.; Rognlien, T.
Highlights: New calibrated DIII-D divertor flow images of C 2 + and He II with Coherence Imaging. The ion flows, 30 km/s, flip in response to reversing the toroidal magnetic field. He (main species) flip is expected, C is balance of frictional and forces. UEDGE calculations with full drifts agree with data, but have narrower profiles. Abstract: To explore the influence of drifts on ion flows in the DIII-D divertor and Scrape-Off-Layer (SOL), a calibrated Coherence Imaging System (CIS) views the lower divertor. A new tuneable calibration laser and precision wavemeter provide the rest wavelength for CIII 465 nm plasma emissions resulting in ≤ 1 km/s uncertainty in ion velocities that are in the range of 30 km/s in the divertor plasma. The 2-D line-integrated velocity images have been tomographically inverted to obtain maps of ion velocity. Both He + and C 2 + ion velocity maps were measured in both directions of the toroidal magnetic field BT, and C 2 + images were obtained in attached and detached L- and H-mode plasmas. The measured C 2 + velocities are in the range of 20–30 km/s and are compared with UEDGE modeling with full drifts. While He II as a main ion is expected to be entrained in the plasma flow, the C 2 + impurity flow involves the competition between the frictional and ion temperature gradient forces. Both the CIS data and UEDGE modeling agree that the C 2 + flow is towards the divertor plates, but flips with the direction of BT . In general, the experimental C 2 + emission and flow profiles have a wider spatial extent than the UEDGE modeling.